Utilization of Carob Bean Pulp and Seeds in Preparing Functional CupCake and Tortilla Bread - Saad, A. Mahgoub (Food Technology Research Journal, 2023)
Developing a technology to produce functional bakery products with increased nutritional value, considering the constantly growing number of people who, for health reasons, are forced to follow functional food, poses a challenge to the food business. Which encouraged to investigate the possibility of (i) utilizing roasted carob powder (130° C/ 30 min) from carob bean pulp as a natural sweetener to replace sugar at 0, 25, 50, and 75% in cacao cupcakes formula; (ii) utilizing carob bean gum from carob bean seeds as a by-product of pods in tortilla bread at 0, 0.5, 1.0 and 1.5%; and (iii) evaluating the sensory, physicochemical and texture properties of the produced cupcakes and gluten-free bread. Roasted carob powder had significant total phenols (205.53 mg/100g) and antioxidant activity (91.78%). The aqueous dispersion (1%) of carob bean gum showed pseudoplastic behavior with an apparent viscosity (η) from 2110to 438.33 cP. Cupcakes with roasted carob powder up to 50% showed a significant increase in compositional nutrients of the protein, ash, and fiber and a non significant increase in appearance, crust color, crumb texture, odor, and acid value compared with the control sample. Gluten-free bread with carob bean gum up to 1%exhibited significant soft texture, shape symmetry, bright color, and higher overall acceptability. This study recommends the utilization of (i) roasted carob powder as a natural sweetener to replace sugar, which may suit a low glycemic diet, and (ii) carob bean gum as a binder in gluten-free bread, which can meet celiac patient needs.